Operational outages and aggregate uncertainty in the federal funds market - Klee, Elizabeth (Journal of Banking & Finance, 2010)
This paper uses operational problems at depository institutions in sending Fedwire payments as a proxy for aggregate uncertainty in end-of-day Fed account positions and then examines funds market behavior on those days. The results suggest that increased uncertainty is associated with a deviation of the federal funds rate from the Federal Open Market Committee’s (FOMC’s) target rate; the magnitude depends on the severity of the difficulty, the payment volume of the affected participant, and the time of day. The intraday standard deviation of the federal funds rate is also affected by operational outages. Moreover, extensions to Fedwire are more likely on days with possible outages, and discount window borrowing picks up on these days as well.